Sensitivities of Near‐field Tsunami Forecasts to Megathrust Deformation Predictions. Issue 2 (26th February 2018) - Tung, S.; Masterlark, T.
Abstract: This study reveals how modeling configurations of forward and inverse analyses of coseismic deformation data influence the estimations of seismic and tsunami sources. We illuminate how the predictions of near‐field tsunami change when (1) a heterogeneous (HET) distribution of crustal material is introduced to the elastic dislocation model, and (2) the near‐trench rupture is either encouraged or suppressed to invert spontaneous coseismic displacements. Hypothetical scenarios of megathrust earthquakes are studied with synthetic Global Positioning System displacements in Cascadia. Finite‐element models are designed to mimic the subsurface heterogeneity across the curved subduction margin. The HET lithospheric domain modifies the seafloor displacement field and alters tsunami predictions from those of a homogeneous (HOM) crust. Uncertainties persist as the inverse analyses of geodetic data produce nonrealistic slip artifacts over the HOM domain, which propagates into the prediction errors of subsequent tsunami arrival and amplitudes. A stochastic analysis further shows that the uncertainties of seismic tomography models do not degrade the solution accuracy of HET over HOM. Whether the source ruptures near the trench also controls the details of the seafloor disturbance. Deeper subsurface slips induce more seafloor uplift near the coast and cause an earlier arrival of tsunami waves than surface‐slipping events. We suggest using the solutions of zero‐updip‐slip and zero‐updip‐slip‐gradient rupture boundary conditions as end‐members to constrain the tsunami behavior for forecasting purposes. The findings are important for the near‐field tsunami warning that primarily relies on the near‐real‐time geodetic or seismic data for source calibration before megawaves hit the nearest shore upon tsunamigenic events. Key Points: Heterogeneous domain of elastic fault model alters the prediction of seafloor deformation and tsunamis Trench‐breaking boundary condition of geodetic inverse analysis controls the resolved seismic and tsunami sources Finite element deformation models account for realistic slab curvature, bathymetry, and tomography‐based crustal material distribution